Extraction bioethanol from culture medium - Горупа, В. В. (Problems of Environmental Biotechnology, 2013)
The article presents the urgency of biobutanol as a fuel in Ukraine and the production technology. The main stages of production, identify promising areas for improving the process are shown. The paper presents a new technology of biobutanol production that is less expensive with improved process of product extraction from cultural liquid.